The Effect of the Effectiveness of Application and Technical Capabilities of Siopskom Users on the Performance of AMC Officers at Yogyakarta International Airport - Theresia Siul; Fryda Fatmayati (CV. Rayyan Dwi Bharata, 2023)
AMC is the unit responsible for regulation and supervision of order, safety of traffic movement on the apron, and aircraft parking placement, managing all vehicle movements on the apron. To increase the effectiveness of AMC performance, it is necessary to have an information system, namely siopskom to help provide every work convenience for employees. The purpose of this research is to find out how much effectiveness the application has on the performance of AMC officers, to find out the techniques of using SIOPSKOM on the performance of AMC officers, and to find out how much is the effectiveness of the implementation and technical ability of the siopskom user on the performance of AMC officers at Yogyakarta International Airport. This study used a quantitative method with the variables of application effectiveness (X1), the technical ability of Siopskom users (X2) and the performance of AMC officers (Y). The data used are primary data, secondary data, and documentation. Primary data was obtained from distributing questionnaires to 15 AMC officers, secondary data was obtained from taking references from previous studies that were relevant to the research being carried out, and the documentation was in the form of pictures of filling out the questionnaire. Data analysis was used using multiple linear regression tests. The results of the study from the average value on the indicator of the effectiveness of implementation (X1) there is no significant effect between the effectiveness of the application on the performance of AMC officers at Yogyakarta International Airport. There is a significant influence between the Siopskom user's technical ability variable on the performance of AMC officers at Yogyakarta International Airport by looking at the t count value of 6.024 t table of 2.160. Meanwhile, the effectiveness of the implementation and the technical ability of Siopskom users simultaneously affect the performance of AMC officers at Yogyakarta International Airport. Data analysis uses multiple linear so that it produces an f-count value of 24,944 Ftable 0.263 and a significance of 000 0.05.